The Study of Jurisprudential and Legal Foundations of Sharia Supervision and Strategies of Implementing It in the Islamic Banking System - zeinab navabi moghadam; Ali Zare; ahmad yousefi sadeghloo; jafar jamali (مطالعات فقه و حقوق اسلامی)
Considering its nature, Islamic banking requires a special type of monitoring methods in order to adapt the activities of the banking system to the principles and laws of Sharia. In this research, it has been tried to justify the necessity of sharia supervision in the banking system with jurisprudential bases such as the rule of of gharar, prohibition of usury, harm, preservation of public interests, and the lack of innocence of the rulers and numerous legal documents such as the two, four and seventy-first principles of the constitutional law. The basic as well as the existential philosophy of approving the law on banking operations without usury and other related regulations, the necessity of Sharia supervision in this field should be emphasized and examined. International Islamic financial institutions have presented solutions for the implementation of the mentioned institution in the banking system of Islamic countries, which have been implemented in most of the countries with Islamic banking structure. In Iran, during the last few years, we have witnessed the relative stabilization of a position with supervisory, executive and legislative dignity for the Sharia inspector; but the country's banking system is still at the beginning of the path until it is implemented and the results of Sharia supervision are realized. Removing obstacles and providing solutions for the implementation of Sharia supervision requires examining the jurisprudential foundations, explaining the solutions and training for its implementation, which is also the purpose of this research. In this research, the above issue has been discussed and investigated by relying on the descriptive-analytical method from the point of view of legal jurisprudence.